STUDI DESKRIPTIF LITERASI FISIK SISWA FASE A PADA PEMBELAJARAN PJOK DI SEKOLAH DASAR - Vanny Ramadani Ilhania; Lukmannul Haqim Lubay; Wulandari Putri; Achmad Syakur Fahri (Universitas Hamzanwadi, 2026)
The low level of physical fitness among Indonesian children with 77.12% falling into the “inadequate” category calls for strengthening physical literacy from an early age, particularly among early-grade students (Phase A) in rural areas, which have been understudied. This study aims to describe the physical literacy profiles of Phase A students in elementary school, analyze differences in achievement by gender, and identify achievement levels in each domain. Using a quantitative approach with a descriptive design, the study involved the entire population of first- and second-grade students at SDN 2 Sukakarya and SDN 2 Sukalaksana, Samarang Subdistrict, Garut Regency, with a total sample of 206 students selected through total sampling. Data were collected using the adapted Physical Literacy in Children Questionnaire (PL-C Quest) and analyzed using descriptive statistics (percentages). The results showed that the majority of students (54%) fell into the moderate category, 43% into the high category, and 3% into the low category, with no significant difference between boys and girls (t=0.847; p>0.05). Achievement by domain showed that the social domain was the highest (88%), followed by the psychological (80.1%), cognitive (78.4%), and physical (67%), which was the lowest. The study concluded that Phase A students already possess a basic foundation in physical literacy; however, the development of the physical domain still needs to be encouraged through a fun, child-centered learning approach.